Financing risk in the execution of public infrastructure through NEC 3 contracts option F - Ugarte Carmelino, Ameth (2023)
The use of standardized contracts in the implementation of public infrastructure projects has marked a milestone in infrastructure investment policies in Peru. Since 2019, New Engineering Contracts (NEC) have been the ones that have had significant use in construction projects in which one of the contracting parties is the Peruvian State. Therefore, the need arises to study financing risk management and its specific regulation in this type of contract. Given the importance of correct financing risk management in a NEC contract, this article will analyze the related duties and obligations, as well as the origin and consequences of the well-known.